Isolation and Characterization of Endophytic Bacteria in Ciplukan Plant (Physalis angulata) - Annisa Wulan Agus Utami; Munarti Munarti (Indonesian Journal of Biology Education, 2020)
Biodiversity of endophytic bacteria is a potential biological resource to be applied in various fields, especially in the medical field. Endophytic bacteria are bacteria that live in the host plant tissues which belongs to a symbiosis of mutualism. Ciplukan plant (Physalis angulata) is a herbal plant that is useful as antihyperglycemic, antimicrobe, immunostimulant, anti-inflammatory, antioxidant, and cytotoxic. Active compounds obtained from plants need a more complicated time and process compared to extracting compounds from bacteria. The study aims to obtain isolates and characterization of endophytic bacteria in Ciplukan plant (Physalis angulata). The method that is used is the isolation of microbe by Nutrient Agar (NA), and morphological characterization with a gram staining technique. The result of isolation of endophytic bacteria in Ciplukan plant (Physalis angulata) obtains the data which the highest mean is in the rhizosphere part that is 13.13 x 106. Isolation of a single colony of endophytic bacteria obtains 20 bacterial isolates which are 12 bacterial isolates of Gram-positive and 8 bacterial isolates of Gram-negative. The result of isolation of a single colony obtains 1 bacterial isolate of endophytic root (AC2) that has characteristic as Actinobacteria which has a form of spherical spore of colony and Gram-positive. Actinobacteria colonies grow by attached to the surface of the media and can produce spores such as powder. Metabolite compounds produced by Actinobacteria have the role of inhibiting the growth of bacteria and fungi. Furthermore, the metabolites produced by Actinomycetes are widely developed as medicinal materials that can cope with various diseases.